A human laterality disorder caused by a homozygous deleterious mutation in MMP21. Issue 12 (1st October 2015) - Perles, Zeev; Moon, Sungjin; Ta-Shma, Asaf; Yaacov, Barak; Francescatto, Ludmila; Edvardson, Simon; Rein, Azaria JJT; Elpeleg, Orly; Katsanis, Nicholas
Abstract : Background: Laterality in the vertebrate embryo is determined by left-right asymmetric gene expression driven by the flow of extraembryonic fluid across the embryonic node. Defects in these processes cause heterotaxy, the abnormal formation and arrangement of visceral organs that can range from complete inversion of symmetry to the selective misarrangement of organs. However, our understanding of the genetic causality for laterality defects in human beings remains relatively limited. Methods: We performed whole exome sequencing in a consanguineous family with heterotaxia. To interrogate the pathogenic potential of the discovered variant, we used an in vivo system in which the potential of the candidate gene to induce L-R asymmetry was tested by transient suppression and CRISPR/Cas9-induced deletions. We also used in vitro assays to test a possible link between our exome-derived candidate and Notch signaling. Results: We identified a homozygous 2 bp deletion in MMP21, encoding matrix metalloproteinase-21, as the sole coding mutation that segregated with the phenotype. Transient suppression or CRISPR/Cas9-mediated deletion of mmp21 in zebrafish embryos induced cardiac looping defects, with concomitant disruption of laterality markers in the lateral plate mesoderm and disrupted notch signalling in vitro and in vivo. Conclusions: Our data implicate loss of MMP21 as a cause of heterotaxy in humans with concomitant defects in Notch signaling. In support of this finding, a homozygous missense mutation in MMP21 was identified previously in mice with N-Ethyl-N-Nitrosourea (ENU)-induced heterotaxy. Taken together, these observations suggest a role of matrix metalloproteinases in the establishment of asymmetric organ development, likely through the regulation of morphogenetic signals.